2017
DOI: 10.1002/pra2.2017.14505401016
|View full text |Cite
|
Sign up to set email alerts
|

Constructing knowledge and ignorance in the social information worlds of young mothers

Abstract: The socially constructed information worlds within which individuals live, work and play necessarily shape their information practices. One way in which this occurs is through the social construction of knowledge, expertise and ignorance, including which actors are considered to possess authoritative knowledge through administrative authority or lay expertise. Using Adele Clarke's situational mapping techniques, this paper examines the discursive construction of knowledge and ignorance in the information world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Among the myriad approaches to discourse analysis that exist, the specific method we selected was SA [43], a postmodern grounded theory technique that involves diagramming of codes. SA can be applied to either textual or visual data (for textual example, see Greyson et al [44]) and is intended for ‘analysis of extant visual discourse materials on their own and/or as a related part of an integrated multicite/multiscape research project’ [43], making it ideal to explore as an add-on for secondary analysis of IWMs originally created to meet data elicitation objectives.…”
Section: Methodsmentioning
confidence: 99%
“…Among the myriad approaches to discourse analysis that exist, the specific method we selected was SA [43], a postmodern grounded theory technique that involves diagramming of codes. SA can be applied to either textual or visual data (for textual example, see Greyson et al [44]) and is intended for ‘analysis of extant visual discourse materials on their own and/or as a related part of an integrated multicite/multiscape research project’ [43], making it ideal to explore as an add-on for secondary analysis of IWMs originally created to meet data elicitation objectives.…”
Section: Methodsmentioning
confidence: 99%
“…Frazier () appears to have brought Proctor's typology of conceptions of ignorance into the information science literature, suggesting intersections and distinctions between agnotology and elements of Chatman's theory of information poverty (Chatman, ). Greyson, O'Brien, and Shoveller () carried this line of thinking forward in an empirical analysis of the constructions of knowledge and ignorance in social worlds, documenting active and power‐laden negotiations around what is defined as knowledge and expertise. In this analysis, Chatman's theories were again invoked, as the authors identified cases in which marginalized knowledge (for instance, regarding traditional parenting practices) was classified as ignorance, as well as examples of “strategic ignorance practices such as secrecy, apathy and disinformation” (Greyson et al, , p.140).…”
Section: Ignorance Agnotology and Social Informaticsmentioning
confidence: 99%
“…Societally, young mothers have been cast as naïve about sex and contraception (Duncan, 2007;Whitley & Kirmayer, 2008), while young fathers have been labeled as absentee and uninvolved (Duncan, 2007). Although young parents may have similar information needs and practices as older parents, they are often labeled as "information poor" (Greyson, O'Brien & Shoveller, 2017a;2017b) and perceived to be lacking the information needed to make informed decisions. This stigma intensifies the degree to which young parents are monitored by health, education and social service authorities and society more broadly, and bolsters the argument that young parents need information and services to help them navigate pregnancy, birth and parenting (Carson et al, 2017;Greyson, 2012;Greyson et al, 2017a;2017b;Mann, Pearl & Behle, 2004).…”
Section: Young Parents' Information Practicesmentioning
confidence: 99%
“…Because they are perceived to need information, young mothers have access to a variety of "wrap around services," i.e. young parent and pregnancy outreach programs, which provide a variety of information and resources on an array of topics (Greyson et al, 2017a;2017b). There has been a rise in research regarding the experiences of young fathers over the past decade (Dallas, 2009;Davies & Neale, 2015;Davies, 2016;Deslauriers, Devault, Groulx, & Sévigny, 2012;Kirven, 2014;Kiselica & Kiselica, 2014;Sopcak, 2013).…”
Section: Young Parents' Information Practicesmentioning
confidence: 99%
See 1 more Smart Citation